Comparison of Depolarization and Repolarization Parameters in Left vs. Right Ventricular Septal Pacing—An Intraprocedural Electrocardiographic Study - Catalin Pestrea; Ecaterina Cicala; Madalina Ivascu; Alexandra Gherghina; Florin Ortan; Dana Pop (Journal of Cardiovascular Development and Disease, 2023)
Compared with conventional right ventricular septal pacing (RVSP), several studies have shown a net clinical benefit of left bundle branch area pacing (LBBAP) in terms of ejection fraction preservation and reduced hospitalizations for heart failure. The purpose of this study was to compare acute depolarization and repolarization electrocardiographic parameters between LBBAP and RVSP in the same patients during the LBBAP implant procedure. We prospectively included 74 consecutive patients subjected to LBBAP from 1 January to 31 December 2021 at our institution in the study. After the lead was placed deep into the ventricular septum, unipolar pacing was performed and 12-lead ECGs were recorded from the distal (LBBAP) and proximal (RVSP) electrodes. QRS duration (QRSd), left ventricular activation time (LVAT), right ventricular activation time (RVAT), QT and JT intervals, QT dispersion (QTd), T-wave peak-to-end interval (Tpe), and Tpe/QT were measured for both instances. The final LBBAP threshold was a 0.7 ± 0.31 V at 0.4 ms duration with a sensing threshold of 10.7 ± 4.1 mV. RVSP produced a significantly larger QRS complex than the baseline QRS (194.88 ± 17.29 ms vs. 141.89 ± 35.41 ms, p < 0.001), while LBBAP did not significantly change the mean QRSd (148.10 ± 11.52 ms vs. 141.89 ± 35.41 ms, p = 0.135). LVAT (67.63 ± 8.79 ms vs. 95.89 ± 12.02 ms, p < 0.001) and RVAT (80.54 ± 10.94 ms vs. 98.99 ± 13.80 ms, p < 0.001) were significantly shorter with LBBAP than with RVSP. Moreover, all the repolarization parameters studied were significantly shorter in LBBAP than in RVSP (QT—425.95 ± 47.54 vs. 487.30 ± 52.32; JT—281.85 ± 53.66 vs. 297.69 ± 59.02; QTd—41.62 ± 20.07 vs. 58.38 ± 24.44; Tpe—67.03 ± 11.19 vs. 80.27 ± 10.72; and Tpe/QT—0.158 ± 0.028 vs. 0.165 ± 0.021, p < 0.05 for all), irrespective of the baseline QRS morphology. LBBAP was associated with significantly better acute depolarization and repolarization electrocardiographic parameters compared with RVSP.